ANALISIS PERUBAHAN TROPICAL TROPOPAUSE LAYER DI BENUA MARITIM INDONESIA - Indah Susanti; Sinta Berliana Sipayung (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Temperature is an important parameter in climate change, and the temperature changes not only occur on the surface of the earth only. Tropical Tropopause Layer (TTL), a region which has the characteristic troposphere and stratosphere, a critical part of the atmosphere, a layer in the tropics between the main convective outflow level and the cold point, about 12-18 km. This study aims to identify changes occurring in the TTL that are focused on temperature and pressure parameters that are indicator for changes in other parameters. Using Atmospheric Infrared Sounder (AIRS) version 6 data with 1 km vertical resolution, 1-degree horizontal resolution, and monthly temporal resolution (from 2003 to 2015), analyzed TTL changes over Indonesia (80 - 150ËšBT and 20ËšLS - 20ËšLU). Based on the time series analysis, show increasing temperature and pressure in the TTL. The analysis results show that TTL characteristics, influenced by convective processes and radiative processes.Keywords: climate change, tropical tropopause layer, temperature, pressure, convection, radiation.